Revisiting global welfare regimes: Gender, (in)formal employment and care - Roumpakis, Antonios (Social Policy and Society)
Gender critiques of comparative welfare state research have so far predominantly focused on OECD countries but less so in countries across Africa, Asia and Latin America. Existing comparative social policy research in these regions often cites the importance of informal networks and family for social protection but less attention is paid into gender relations and their importance for the social reproduction of these welfare regimes. The article comparatively analyses gender differences in the sphere of production (captured by the gender gap in formal and informal employment) and social reproduction (captured by time spent on unpaid domestic work). The article identifies regional patterns and explores implications for women$1 (Bs ability to access welfare and the labour market. Additionally, it shows that informal activities (employment, domestic work) are extensive among many African, Asian, Latin American, but also specific OECD, welfare regimes. The article contributes first by incorporating gender in the analysis of global welfare regime and second by highlighting the importance of informal relationships for the analysis of welfare regimes. - Reproduced s
Keywords: Gender, Global welfare regimes, Informal, Care, Employment